Rethinking the Russo-Japanese War, 1904-5 : Volume 2: The Nichinan Papers. - Chapman, John W. M. (BRILL, 2007)
This volume brings together a set of original essays by Japanese, Korean and Chinese scholars, together with analyses by Russian, US and European specialists, thereby reflecting the multinational mix of contemporary influences forming the international vortex of the war.